Dissecting the Spatial and Single‐Cell Transcriptomic Architecture of Cancer Stem Cell Niche Driving Tumor Progression in Gastric Cancer - Guangyu Zhang; Xin Zhang; Wenting Pan; Xizhao Chen; Lingfei Wan; Chunjie Liu; Yuting Yong; Yue Zhao; Shuli Sang; Lihua Zhang; Sheng Yao; Yushu Guo; et al. (Advanced Science)
Abstract Despite significant advancements in identifying novel therapeutic targets and compounds, cancer stem cells (CSCs) remain pivotal in driving therapeutic resistance and tumor progression in gastric cancer (GC). High‐resolution knowledge of the transcriptional programs underlying the role of CSC niche in driving tumor stemness and progression is still lacking. Herein, spatial and single‐cell RNA sequencing of 32 human gastric mucosa tissues at various stages of malignancy, illuminating the phenotypic plasticity of tumor epithelium and transcriptional trajectory from mature gastric chief cells to the CSC state, which is associated with activation of EGFR and WNT signaling pathways, is conducted. Moreover, the CSCs interact with not only the immunosuppressive CXCL13+ T cells and CCL18+ M2 macrophages to evade immune surveillance, but also the inflammatory cancer‐associated fibroblasts (iCAFs) to promote tumorigenesis and maintain stemness, which construct the CSC niche leading to inferior prognosis. Notably, it is uncovered that amphiregulin (AREG) derived from iCAFs promotes tumor stemness by upregulating the expression of SOX9 in tumor cells, and contributes to drug resistance via the AREG‐ERBB2 axis. This study provides valuable insight into the characteristics of CSC niche in driving tumor stemness and progression, offering novel perspective for designing effective strategies to overcome GC therapy resistance.